Volatiles and Antioxidant Activity of Citrus Fiber/Blackberry Gels: Influence of Sucrose and Trehalose - Mirela Kopjar; Ivana Ivić; Ivana Buljeta; Ina Ćorković; Josipa Vukoja; Josip Šimunović; Anita Pichler (Plants, 2021)
Citrus fiber/blackberry gels (CBg) can be used for the preparation of various bakery products as well as confectioneries. The objective of this study was to evaluate the influence of the type of disaccharides (sucrose or trehalose) and their percentages (10% or 20%) on volatile compounds as well as phenolics, antioxidant activity and color of formulated CBg. Additionally, CBg were stored at room temperature for 3 months to evaluate their stability. Both disaccharides type and their percentage affected the investigated parameters. Sucrose had a higher positive impact on volatiles after formulation and storage of CBg, while trehalose had a higher positive impact on total phenolics. Amounts of phenolics increased with the increase of disaccharides amount, while the behavior of volatiles also depended on volatiles’ properties. Results of this study emphasized the importance of the adequate choice of ingredients for the formulation of high-quality fruit products.